Designing curriculum to shape professional social media skills and identity in virtual communities of practice. (January 2017) - Novakovich, Jeanette; Miah, Sophia; Shaw, Steven
Abstract: A broad range of professional communicators employ social media as a professional practice; however research indicates that it has yet to become a prevalent component in professional writing courses. Additionally, the competencies surrounding social media practices and the pedagogy to incorporate such competencies are not well established. Compounding this shortcoming is the problematized nature of social media technologies for learners as being a source of their personal identity; thus instructors must transform learners' everyday practices that inform their personal identity into professional practices that will inform their professional identity. This article reports on the first iteration of a four-year design-based study exploring the following research questions: What challenges might students face when transforming everyday social media practices into professional practice? How can social media technologies facilitate professional identity formation? The results indicated that introducing professional social media skills into the curriculum provoked a significant amount of resistance on the part of learners. In general, the students lacked agency on social networks and required guidance when articulating modes of online authenticity. The study also discovered an alarming gap between students' everyday practices on social networks and professional practice. Through course intervention and reflexivity on the part of the students, final results demonstrated a remarkable growth in terms of research participants' beliefs, engagement, insights and goals regardingthe usage of social media. Graphical abstract: Highlights: Operationalized a social media component for a professional writing course. Closed the gap between learners' personal and professional practices. Tested an instructional design that employed heutagogical learning principles. Identified barriers to performance influencing participation in vCoP. Incorporated a vCoP to foster online professional identity formation.